(untitled) (Academia Science Repository, 2023)
The importance of preserving natural ecosystems in the conditions of modern ecological crisis. The analysis of the problem of development of the concepts of "environmental competence" and "environmental competence" is given. The structural components of environmental competence, the conditions for its formation on the basis of the activity approach are considered. The dominance of the subjective attitude to nature among university students has been practically studied.